1998
DOI: 10.1038/sj.mp.4000400
|View full text |Cite
|
Sign up to set email alerts
|

Further support for an association between a polymorphic CAG repeat in the hKCa3 gene and schizophrenia

Abstract: A recent study has suggested that a polymorphism in the hKCa3 potassium channel may be associated with raised susceptibility to schizophrenia. 1 Despite its modest statistical significance, the study 1 is intriguing for two reasons. First, hKCa3 contains a polymorphic CAG repeat in its coding sequence, with large repeats more common in schizophrenics compared with controls. 1 This is interesting in view of several repeat expansion detection (RED) studies 2 that have reported an excess of large CAG repeats in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
49
3
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 11 publications
9
49
3
1
Order By: Relevance
“…It is noteworthy that the hSKCa3 gene has also been implicated in schizophrenia and bipolar disorders. 6,[14][15][16][17] Although the phenotype of AN and the major psychoses vary considerably, our results may support the hypothesis of common susceptibility genes shared by several psychiatric disorders. Thus, drugs active at the hSKCa3 channel could be considered in the pharmacotherapy of some neuropsychiatric disorders.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…It is noteworthy that the hSKCa3 gene has also been implicated in schizophrenia and bipolar disorders. 6,[14][15][16][17] Although the phenotype of AN and the major psychoses vary considerably, our results may support the hypothesis of common susceptibility genes shared by several psychiatric disorders. Thus, drugs active at the hSKCa3 channel could be considered in the pharmacotherapy of some neuropsychiatric disorders.…”
supporting
confidence: 77%
“…24 The distribution of the alleles in our control population was similar to that previously found in other populations. 6,[15][16][17][18] Comparison of the AN to the control alleles revealed a broad overlap with differences in only one or two CAG repeats in average and modal length. This overlap is not surprising for a common, heterogeneous and probably multifactorial disorder, such as AN.…”
mentioning
confidence: 99%
“…The modal repeat length for both patient and control groups is 19 CAG repeats, as reported in European and North American Caucasians. 8,9 A slight bimodal character is evident in these distributions, with a smaller peak present at 12-14 repeats, as has also been reported in two previous studies. 8,9 The two longest alleles (23 and 24 repeats) are uniquely represented among patients.…”
Section: Association Between Length Of Cag Repeats In Hkca3/kcnn3 Andsupporting
confidence: 66%
“…The second polyglutamine repeat is highly polymorphic in Caucasian European and North American populations, ranging from 10-28 repeats in length, with a modal value of 19 repeats. 8,9 Case-control studies have recently shown a significant over-representation of longer hKCa3/KCNN3 CAG-repeat alleles in Caucasian schizophrenia patients compared with ethnically matched controls, although there is considerable overlap in allele sizes, and the modal allele has 19 repeats for all these populations. 8,9 In this report we firstly confirm the previously described association between the presence of longer CAG repeats in the hKCa3/KCNN3 gene and schizophrenia in Israeli Ashkenazi Jews.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation